A Multilevel and Spatial Analysis of the Infant and Young Child Feeding Practices and Associated Factors among the Under-2 Aged Children in Bangladesh. Issue 2 (3rd April 2022) - Khan, Jahidur Rahman; Awan, Nabil; Sheikh, Md Tuhin
ABSTRACT: Infant and young child feeding (IYCF) is crucial for the growth, development, and survival of a child. This study aims to examine the factors associated with IYCF practices among the under-2 aged children in Bangladesh and spatial variability. A total of 2336 children aged 6–23 months were selected from the 2014 Bangladesh Demographic and Health Survey (BDHS). A multi-level logistic regression was used to determine the association between socio-demographic and health-related factors accounting for the cluster effects. An adaptive bandwidth kernel density estimator (KDE) was used to investigate the spatial variability of IYCF practices in Bangladesh. The prevalence of minimum dietary diversity (MDD), minimum meal frequency (MMF), and minimum acceptable diet (MAD) were 29%, 47%, and 19% respectively, where the suboptimal IYCF practice was 96% among them. The study findings show that higher maternal age at childbirth and maternal education level are positively associated with MDD, MMF, and MAD. The likelihood of MMF and MAD was higher for children whose mothers had the decision-making abilities (adjusted odds ratio, [AOR] 1.23 and 1.26, respectively) and had exposure to media (AOR 1.43 and 1.38, respectively). Four or more antenatal care (ANC) visits positively associated with the MDD (AOR 1.47; 95% confidence interval [CI] 1.07–2.02) and ICFI (AOR 3.06; 95% CI 1.24–7.54). The heatmap shows Northern parts of Bangladesh performed better than South-West parts in child feeding practices. Overall, age-appropriate IYCF practices are not satisfactory, and many maternal characteristics contribute significantly to this. Geospatial inequalities are also notable across Bangladesh. The current scenario reinforces the need for programmes and interventions that address the spectrum of IYCF practices and help reduce spatial disparities.